ESTROGEN RECEPTOR, PROGESTERONE RECEPTOR & Her-2/ NEU POSITIVITY AND IT’S ASSOCIATION WITH TUMOR CHARACTERISTICS - Shazia Aslam; Sadia Hameed; Arif Hussain (Journal of University Medical & Dental College, 2016)
ABSTRACT: BACKGROUND: Breast carcinoma is the most frequent malignancy of females which is worldwide in its distribution and is the second most common cause of cancer related deaths in females. In Pakistan it occurs more commonly in young ladies as compared to western women where it is more prevalant in older age group. The objectives of this study were to determine the frequency of ER, PR positivity& HER-2/neu receptor over-expression and its association with some of the characteristics of breast cancer like patient age, tumour size, histological grade and axillary lymph node involvement. OBJECTIVE: To determine the receptor status of breast carcinoma and analyze them in correlation with tumor characteristics in women of District Faisalabad. STUDY SETTING: The sample consisted of 123 surgical specimens of patients who had the diagnosis with invasive breast cancer received from January 2011 to January 2013. METHODS: This study was conducted at Pathology Department of UMDC, Faisalabad & Meezan Lab Faisalabad from January 2011-13. Surgical specimens of patients with breast cancer who had undergone Modified Radical Mastectomy (MRM) sent to the histopathology labs were included in the study. The representative sections from resected specimens were referred for immunohisto-chemical (IHC) studies (HER-2/neu receptor and ER/PR) after detailed histopathological review. Patients who had refused for ER, PR & HER-2/neu receptor immunohistochemistry were not included in this study. Data was analyzed by SPSS version 16. RESULTS: The study included comprised of surgical specimens of 123 cases of breast carcinoma who had undergone modified radical mastectomy. The mean age of the patients included in this study was 46 years and majority of the patients were in 4th decade of life. Estrogen receptor positivity was observed in 58.53% cases. Progesterone receptor was positive in 52.03% cases. The over expression of Her-2/neu protein was seen in 52.03%. Hormone receptor positivity and positivity, over-expression of HER-2/neu was not significant in relation to histopathological sub-type (p>0.05), number of axillary lymph nodes with metastatic IDC (p>0.05) and tumor size (p>0.05). It had a significant association with histological grade (p<0.05). CONCLUSION: Hormone receptor status and Her-2/neu expression should be assesed in all patients of breast carcinoma because it carries high prognostic significance and is reported more prevalent in Pakistani women. Thus the positive cases of Her-2/neu may be offered Herceptin therapy and derive benefit from the specific chemotherapeutic agents. Similarly the ER, PR positive cases should get anti-estrogen therapy which can improve survival in these patients. This is more cost effective and will avoid unnecessary use of drugs